2015
DOI: 10.1371/journal.pone.0140069
|View full text |Cite
|
Sign up to set email alerts
|

Study of Malformin C, a Fungal Source Cyclic Pentapeptide, as an Anti-Cancer Drug

Abstract: Malformin C, a fungal cyclic pentapeptide, has been claimed to have anti-cancer potential, but no in vivo study was available to substantiate this property. Therefore, we conducted in vitro and in vivo experiments to investigate its anti-cancer effects and toxicity. Our studies showed Malformin C inhibited Colon 38 and HCT 116 cell growth dose-dependently with an IC50 of 0.27±0.07μM and 0.18±0.023μM respectively. This inhibition was explicated by Malformin C’s effect on G2/M arrest. Moreover, we observed up-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Asperazine was reported to have significant in vitro cytotoxicity against human leukemia [ 52 ] but no in vivo including bioavailability studies confirmed this. Malformins are currently being investigated for anti-cancer drug potential [ 53 ]. Altogether there are very few studies on other effects than in-vitro or in older studies intraperitoneal injection of compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Asperazine was reported to have significant in vitro cytotoxicity against human leukemia [ 52 ] but no in vivo including bioavailability studies confirmed this. Malformins are currently being investigated for anti-cancer drug potential [ 53 ]. Altogether there are very few studies on other effects than in-vitro or in older studies intraperitoneal injection of compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Malformin A1 ( 114 ) from Aspergillus niger and Aspergillus tubingensis showed malformation activity in the corn root, and cytotoxic activity, and anti-TMV activity [ 89 , 90 , 92 , 93 ]. Malformin C ( 119 ) from Aspergillus niger had potent cell growth inhibition activity [ 94 ], but its therapeutic index was too low to be an anti-cancer drug [ 95 ].…”
Section: Cyclic Pentapeptidesmentioning
confidence: 99%
“…Malformin C has been previously detected in isolates of Aspergillus niger [27,28] and A. tubingensis [29,30], but not in A. welwitschiae . Genomics-wise, a single protein has been described as essential for the synthesis of this compound [18], which we used as a reference in our analysis.…”
Section: Discussionmentioning
confidence: 99%